Pendidikan Karakter dalam Al-Qur’an dan Ilmu Sains - Dian Nirmala Sofi; Meza Aulia Zahrah; Mifta Yuljannah P; Nurfadilah Nurfadilah; Reva Nur Amalya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This journal talks about character education in the Koran and science. The aims of this journal are (1) to understand the definition of character education, (2) to know how Islam views character formation through the Al-Qur'an and science, (3) to study Islamic ethics, and (4) to know the principles of Islamic ethics. This journal was prepared using library research methods, by collecting and analyzing material from various books.